Research on a Focused Acoustic Vortex that Can Be Used to Capture Tiny Underwater Objects - Li, Zhengbao; Hu, Gehao; Wang, Qingdong; Du, Libin (Water (Basel), 2024)
The energy of a focused acoustic field is quite concentrated, and the ability of an acoustic vortex formed by a concave focusing transducer array to capture objects in a flowing medium remains to be investigated. In this paper, the focused pressure distributions generated by an acoustic lens and a concave focused transducer array are firstly simulated, and the analyzed results show that the focusing effect of the latter is significantly better than that of the former. The acoustic gradient force and orbital angular momentum density distributions of the focused transducer array were investigated. A focused acoustic vortex tiny object capture system was built by simulating the hydrothermal column that forms in the seafloor hydrothermal zone. It was discovered that the forces affecting microorganisms and other small objects primarily consist of acoustic gradient force, viscous force, and additional mass force. The non-destructive capture of tiny seafloor objects was accomplished by adjusting the focused acoustic vortex’s propagation direction and the transducer array’s emitted power, thereby enabling more potential applications in ocean equipment.